Kajian Desa Mandiri Pangan Kabupaten Bekasi - Pipit Septi Fitriyanti; Rizky Afnan Fadillah; Fauziah (Bekasi Development Innovation Journal, 2024)
Abstract Food security is a polemic that often occurs in various villages. The application of the Desa Mandiri Pangan is expected to be a solution to the limited availability of food in the village area, especially villages in Bekasi Regency. Data collection techniques and analysis of secondary data were carried out to obtain an index of village readiness in establishing an independent village food security program. The results of the analysis obtained that some villages have met the criteria for the application of Desa Mandiri Pangan program in Bekasi District. It is necessary to review the process of fulfilling the criteria in several villages so that Desa Mandiri pangan program in Bekasi District can be carried out as a whole. Keywords: village, food security